Development of an in vivo murine model of perineural invasion and spread of cutaneous squamous cell carcinoma of the head and neck - de Lima, Priscila O.; Broit, Natasa; Huang, Johnson D.; Lim, Jae H.; Gardiner, Damien J.; Brown, Ian S.; Panizza, Benedict J.; Boyle, Glen M.; Simpson, Fiona (Frontiers in Oncology, 2023)
Cutaneous squamous cell carcinoma of the head and neck (cSCCHN) can metastasize by invading nerves and spread toward the central nervous system. This metastatic process is called perineural invasion (PNI) and spread (PNS). An in vivo sciatic nerve mouse model is used for cSCCHN PNI/PNS. Here we describe a complementary whisker pad model which allows for molecular studies investigating drivers of PNI/PNS in the head and neck environment. A431 cells were injected into the whisker pads of BALB/c Foxn1nu and NSG-A2 mice. Tumor progression was monitored by bioluminescence imaging and primary tumor resection was performed. PNI was detected by H&E and IHC. Tumor growth and PNI were assessed with inducible ablation of LOXL2. The rate of PNI development in mice was 10%-28.6%. Tumors exhibited PNI/PNS reminiscent of the morphology seen in the human disease. Our model’s utility was demonstrated with inducible ablation of LOXL2 reducing primary tumor growth and PNI. This model consists in a feasible way to test molecular characteristics and potential therapies, offers to close a gap in the described in vivo methods for PNI/PNS of cSCCHN and has uses in concert with the established sciatic nerve model.